Inclusion of New Instructional Strategies in Pre-Service Teacher Training (B.Ed.) Program in Pakistan - Ranjha, Najma; Muqqadas, Khadija (Advances in Social Sciences Research Journal, 2015)
Pakistan has continuously been under criticism as it does not appropriately fulfill the needs and demands of the school context and society. Its pre-service teacher training (B.Ed.) program does not efficiently prepare B.Ed. graduates to impart quality education to the secondary classes. It does not prepare them to work with others to expand their content knowledge, sharpen their instructional skills and build up their capacity to use data for meaningful decision making while its design and practice is based on strong and solid courses (i.e., general education, specialist subjects, education foundation studies, professional studies/content pedagogy as well as satisfactory practicum component). Perhaps these flaws are found in B.Ed graduates due to pay no attention to new instructional strategies during their pre-service teacher training program. This paper examines effectiveness of new instructional strategies and their impact on future teachers.